FUNGSI KEPALA SEKOLAH DALAM PEMBENTUKAN AKHLAK PESERTA DIDIK MELALUI PEMBIASAAN PERILAKU ISLAMI DI SMP NEGERI 2 TAWANGSARI, SUKOHARJO TAHUN PELAJARAN 2016/2017 - Fadlilah, Novica Nur; , Drs. Bambang Raharjo, M.Ag (2017)
In this modern era, the character of education is concerned by the world of education remembering any irregulaties happened in the school, with any irregulaties, it affected students on learning outcomes. Therefore, students should be equipped with a moral in order to avoid irregularities. One of responsible for formation a moral at school was headmaster. The headmaster was a teacher who was get additional role to lead the management of education and effort to improve the quality of school education. Headmaster should be create a safe, peaceful, comfortable so learning proceeded fluently, to spread a good moral on students needed a habituation method. Headmaster did not only have a role as leader, but headmaster should be a role model and motivator for teachers and students. The research used to know effort of headmaster establising moral through the habituation of Islamic behaviour in school. This research used a descriptive qualitative method. The data of this research acquired from interview, observation, and documentation. The result of this research knew effort of headmaster establising moral through habituation of Islamic behaviour. The methods of Islamic habituation were a strategy for the establishment of Islamic moral because this method could form the younger generation so that they had a good personality. The habituations of headmaster were teach to student namely "Senyum, Sapa, Salam" or as known as 3S. Moreover, there were habituation activities such as doing shalat, infaq, praying before and after learning activities than eating together. Through the Islamic habituation, it could form a good character for students and it made students achievement.